Discharge coefficient of a semi-elliptical side weir in subcritical flow - Kaya, Nihat; Emiroglu, M. Emin; Agaccioglu, Hayrullah (Elsevier Sci Ltd, 2011)
A labyrinth weir is an overflow weir, folded in plan view to provide a longer total effective length for a given overall weir width. The total length of the labyrinth weir is typically three to five times the weir width. In this study, a semi-elliptical labyrinth weir was used as a side weir structure. Rectangular side weirs have attracted considerable research interest. The same, however, is not true for labyrinth side weirs. The present study investigated the hydraulic effects of semi-elliptical side weirs in order to increase their discharge capacity. To estimate the outflow over a semi-elliptical side weir, the discharge coefficient in the side weir equation needs to be determined. A comprehensive laboratory study including 677 tests was conducted to determine the discharge coefficient of the semi-elliptical side weir. The results were analyzed to find the influence of the dimensionless weir length L/B, the dimensionless effective length L/l, the dimensionless weir height p/h(1), the dimensionless ellipse radius b/a, and upstream Froude number F-1 on the discharge coefficient. It was found that the discharge coefficient of semi-elliptical side weirs is higher than that of classical side weirs. Additionally, a reliable equation for calculating the discharge coefficient of semi-elliptical side weirs is presented. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Side weir; Discharge coefficient; Intake; Labyrinth; Semi-elliptical; Channel flow